Photonic crystal light collectors in fish retina improve vision in turbid water - Kreysing, Moritz; Pusch, Roland; Haverkate, Dorothee; Landsberger, Meik; Engelmann, Jacob; Ruiter, Janina; Mora-Ferrer, Carlos; Ulbricht, Elke; Grosche, Jens; Franze, Kristian; Streif, Stefan; Schumacher, Sarah; et al. (Science, 2012)
Despite their diversity, vertebrate retinae are specialized to maximize either photon catch or visual acuity. Here, we describe a functional type that is optimized for neither purpose. In the retina of the elephantnose fish (Gnathonemus petersii), cone photoreceptors are grouped together within reflecting, photonic crystal-lined cups acting as macroreceptors, but rod photoreceptors are positioned behind these reflectors. This unusual arrangement matches rod and cone sensitivity for detecting color-mixed stimuli, whereas the photoreceptor grouping renders the fish insensitive to spatial noise; together, this enables more reliable flight reactions in the fish's dim and turbid habitat as compared with fish lacking this retinal specialization.
CRIS-Team Scopus Importer:2020-08-12